Reforming energy subsidy in Kuwait: maximizing net benefits and equity compliance - Mohammad A. Alolayan; Farah Albarrak; Mohammad Abotalib; Mohammad Alshawaf (Kuwait Journal of Science)
The net benefits and public acceptance for a proposed reform to the current subsidization of energy in the State of Kuwait was investigated in this study. The proposal claims to reduce the consumption of utilities (electricity and water) and gasoline. This is expected to improve the ambient air quality and reduce the cost of subsidization. The public health will result in less mortality and morbidity rates. The proposed subsidization suggests that the government pays the consumers the subsidization cost in advance and in exchange for raising the subsidized tariffs to full price. The consumption will likely be reduced by a rate equals the over consumption due to the current subsidized tariffs in relative to the income. The net benefits is expected to be maximized and shifted to a pseudo-equilibrium point where both the governments and the consumers will be better off financially. There is no loser in this scenario, all are winners. The public acceptance toward the proposed strategy was examined using 293 voluntarily one-to-one interviews and utilities meter reading program conducted on 90 houses. The interviews for gasoline and utilities indicated 57% and 66% of the respondents see no equity in the current subsidization, 55% and 80% admitted to overuse, 11% and 20% averages of the over consumptions, and 67% and 66% of the respondents were willing to adopt the new strategy. The consumer is expected to save 762 USD/year from gasoline, and 7,940 USD/year from utilities. The estimated net benefits is 2,845.3 million USD annually with 58% attributed to cost saving and 42% to health benefits. The expected avoided premature deaths from gasoline and utilities are 21 and 62 lives annually. Also, it was estimated that utilities benefits contribute to the net benefits by 68%. The annual concentration of PM2.5 is expected to drop by 2.6 µg/m3.